2011
DOI: 10.1002/hbm.21392
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain activity during emotional empathy in somatoform disorder

Abstract: Somatoform disorder patients suffer from impaired emotion recognition and other emotional deficits. Emotional empathy refers to the understanding and sharing of emotions of others in social contexts. It is likely that the emotional deficits of somatoform disorder patients are linked to disturbed empathic abilities; however, little is known so far about empathic deficits of somatoform patients and the underlying neural mechanisms. We used fMRI and an empathy paradigm to investigate 20 somatoform disorder patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 78 publications
4
32
0
2
Order By: Relevance
“…These authors compared an average response to multiple types of emotional stimuli (angry, fearful, and happy) to neutral stimuli and found greater activation to emotional stimuli in the bilateral anterior STG. These and other studies (de Greck et al, 2012;Pehrs et al, 2013) suggest that STG responds differently to auditory, audiovisual, and visual-only stimuli based on the emotional content of the stimulus. Finally, our results are in agreement with the study by Ding et al (2013), who observed decreased regional structural nodal connectivity strength in STG bilaterally along with several other brain regions as well as globally decreased structural connectivity strength in PNES patients compared to controls.…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)supporting
confidence: 61%
See 1 more Smart Citation
“…These authors compared an average response to multiple types of emotional stimuli (angry, fearful, and happy) to neutral stimuli and found greater activation to emotional stimuli in the bilateral anterior STG. These and other studies (de Greck et al, 2012;Pehrs et al, 2013) suggest that STG responds differently to auditory, audiovisual, and visual-only stimuli based on the emotional content of the stimulus. Finally, our results are in agreement with the study by Ding et al (2013), who observed decreased regional structural nodal connectivity strength in STG bilaterally along with several other brain regions as well as globally decreased structural connectivity strength in PNES patients compared to controls.…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)supporting
confidence: 61%
“…There is a growing body of evidence that the STG is also involved in perception of emotions (de Greck et al, 2012;Husain et al, 2014;Pehrs et al, 2013;Robins et al, 2009). In one fMRI study increased activation in the bilateral STG was observed in response to pleasant or unpleasant sounds when compared to neutral sounds (Husain et al, 2014); HCs showed increased activation in the left STG specifically while listening to pleasant or unpleasant sounds, compared to neutral sounds.…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)mentioning
confidence: 99%
“…58 Reduced insula and amygdala activity was observed during emotional empathy, indicating disturbed emotional processing. 59 However, fibromyalgia, which most closely resembles somatoform pain disorders in many aspects, displays a characteristic connectivity pattern during rest, as recently shown by Cifre and colleagues. 60 They found that functional connectivity of the anterior cingulate, insula and somatosensory regions with amygdala and basal ganglia was enhanced, whereas the interplay between somatosensory and default mode regions was reduced.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, recent study has shown less activity in somatoform patients in the emotional brain circuit, including the bilateral parahippocampal gyrus, the left amygdala, the left superior temporal gyrus, and the insula, during facial emotion recognition. Somatoform patients exhibited increased alexithymia scores (TAS-20) and elevated depression scores (BDI) [97]. Therefore, their neurobiological features to emotional stimuli were more similar to alexithymia.…”
Section: Discussionmentioning
confidence: 99%